(untitled) (BioLaw Journal - Rivista di BioDiritto, 2023)
The article analyzes the impact of climate change on food security and the right to food, exploring different regulatory models deemed to address the challenges produced by climate change in food systems, within the framework of recommendations from international institutions. The essay identifies certain integrated regulatory approaches applicable to agrifood regulation on which a widespread consensus in the scientific community and among international institutions may be appreciated. Among these are the One Health approach, the ecosystem approach, the models inspired by agroecology, and the so-called human rights-based approach (HRB). The paper discusses their effectiveness in promoting food security and climate resilience, attempting to verify the presence of regulatory provisions inspired by such approaches in existing food legislation. In such respect, the article examines the recent European "From farm to fork" strategy and certain approaches in the context of the Global South.